ANALISIS PEMBENTUKAN PORTOFOLIO SAHAM OPTIMAL MENGGUNAKAN MODEL INDEKS TUNGGAL DAN MODEL MARKOWITZ (Studi Kasus Pada Saham Bumn Yang Terdaftar Di Bursa Efek Indonesia) - Erni Maryani; Haryetti '; Errin Yani Wijaya (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
Investment is a growing number of funds in hopes of getting higher returns in the future. To minimize risk, The investment can do in a portfolio. The purpose of this study to analyze the formation of a portfolio of 12 stocks of BUMN buly using single index models and Markowitz models. In addition, by using these two methods can also be known what proportion of funds that should be invested in each stock, in order to provide returns expected by investors by reducing the risk to be borne. Then, test the hypothesis by using t-test. The result of this research in a combination of shares and the proportion of funds is different between the portfolio by using a single index models and portfolio by using Markowitz models, but there is no different in the t-test that the returns generated.Keywords: investment, optimal portfolio, single index models, and Markowitz models.